2010
DOI: 10.1007/s12630-010-9317-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an ultrasound-guided subsartorial approach to saphenous nerve block: a case series

Abstract: Purpose The saphenous nerve, a branch of the femoral nerve, is a pure sensory nerve that supplies the anteromedial aspect of the lower leg from the knee to the foot. There is limited evidence of the effectiveness of ultrasoundguided techniques to block the saphenous nerve. We therefore undertook a retrospective case series to investigate the efficacy of an ultrasound-guided subsartorial approach to saphenous nerve block. Methods During a four-month period, all patients receiving a subsartorial saphenous nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 10 publications
0
30
0
1
Order By: Relevance
“…This is similar to other ultrasound-guided approaches to the saphenous nerve block. 23 A limitation of this study was not taking this relatively low success rate into consideration when powering the study. The inclusion of the perceived block failures in the overall statistical analysis gives a true clinical reflection of the ability of this block to reduce postoperative pain scores in the PACU.…”
Section: Discussionmentioning
confidence: 98%
“…This is similar to other ultrasound-guided approaches to the saphenous nerve block. 23 A limitation of this study was not taking this relatively low success rate into consideration when powering the study. The inclusion of the perceived block failures in the overall statistical analysis gives a true clinical reflection of the ability of this block to reduce postoperative pain scores in the PACU.…”
Section: Discussionmentioning
confidence: 98%
“…This block is frequently used for anesthesia and analgesia of the medial calf and ankle. 6 Recent case reports and a randomized trial have demonstrated superior analgesia after total knee arthroplasty (TKA) in patients receiving ACB compared with parenteral opioids. [7][8][9] Our objective was to determine if an ultrasound-guided ACB can preserve quadriceps strength, thus minimizing weakness of knee extension compared with ultrasound-guided FNB.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 However, in part owing to its small caliber, the saphenous nerve is more difficult to reliably block than the sciatic nerve in the popliteal fossa (ie, with success rates reliably exceeding 95%). [3][4][5] As the terminal branch of the femoral nerve, the saphenous nerve provides sensory innervation to the anteromedial aspect of the lower leg, including the medial ankle joint capsule and distal tibia. 6 Extending proximally from the femoral triangle, it descends within the adductor canal, accompanying the femoral artery and nerve of vastus medialis beneath the sartorius muscle, and continues its course underneath the sartorius muscle until it penetrates the connective tissue between the tendons of the sartorius and gracilis muscles on the medial side of the knee.…”
mentioning
confidence: 99%